Analisis Pengetahuan Lingkungan Peserta Didik MAN 1 Pekanbaru sebagai Madrasah Adiwiyata Nasional - Istiqomah, Istiqomah (Takuana: Jurnal Pendidikan, Sains, dan Humaniora, 2023)
Environmental problems are currently increasing. One way to reduce environmental problems is to change students' perspectives and attitudes to care more about the environment. Adiwiyata school program is one way that can be taken to achieve this goal through learning environmental education (PLH). This study aims to determine the level of environmental knowledge of students at MAN 1 Pekanbaru. The study was conducted at MAN 1 Pekanbaru TP 2020-2021 with a total sample of 217 people, using a survey method with a random sampling technique. The environmental knowledge questionnaire was prepared using ten indicators developed from the PLH syllabus. The analysis showed that the environmental knowledge of MAN 1 students in the high category was 102 people or 47%, the medium category was 87 people or 40.09%, and the low category was 28 people or 12.90%. These results indicate that PLH learning can provide environmental knowledge to students at MAN 1 Pekanbaru.